Land Degradation and Option of Practical Conservation Concepts in Manna Watershed Bengkulu Indonesia - Muhammad Faiz Barchia; Khairul Amri; Renra Apriantoni (TERRA : Journal of Land Restoration, 2018)
Watershed overcoming deteriorates in its function was indicated by increasing soil erosion and land degradation. The research aims were to determine and map critical land degradation levels and to chose options of practical conservation concepts in Manna watershed. The Manna watershed lays on 102°51'38.2" - 103°10'57.8" long, and 04°0'39.6" - 4°29'38.0" alt covering 72,899.9 ha. The analysis procedures to determine land degradation levels based on Ministry of Forestry Rule (No. P.32/Menhut-11/2009), Procedures of Technical Design on Forest and Land Rehabilitation in Watershed (RTkRHL-DAS). The results showed that the Manna watershed divided in three land uses functions namely protected forest, limited timber forest, and agricultural cultivated areas/settlement. The land starting overcome degradation in covered by 35,318.6 ha or 48,77% of the watershed based on digital mapping using ArcGIS 10.1 software. The lands that categorized the critical level of degradation covered 7,989.5 ha or 11,03% of the watershed, and classified in the high critical level were 169.8 ha or 0,23% of the watershed. Options of conservation practice on the degraded lands in the Manna watershed should implement agro-forestry models because of the physiographical landscape in this area covering by waving to hilly landforms. On the protected forest and limited timber forest should develop agro-forestry with collaborative approaches through social engineering and social forestry. Re-establishing land use of the Manna watershed based on functions of land is the wise options for the sustainable environmental concepts